Thermoeconomic analysis of heat and electricity prosumers in residential zero-energy buildings in Finland. (1st July 2017) - Manrique Delgado, Benjamin; Cao, Sunliang; Hasan, Ala; Sirén, Kai
Abstract: Energy planning and management in the built environment should not limit their scope to reaching zero-energy or nearly zero-energy balances: they should aim for cost optimality as well. Only then can environmental and economic sustainability be attained. In this study, a set of energy systems that include exchange with electrical and heating grids are proposed for an existing single-family house in Finland. The simulated energy and exergy balances are quantified, as well as the levelized cost of electricity and levelized cost of heat, the simple payback period and the internal rate of return of the investment. By driving a heat pump to convert surplus electricity into heat and exporting it, an annual energy surplus of 36 kWh/m 2 /a is achievable, whereas by importing heat from a heating grid leads to an annual exergy surplus of 8 kWh/m 2 /a. However, the economic indicators are unattractive: the lowest levelized cost of electricity and simple payback period are 41 cent/kWh and 46 years respectively, while the highest internal rate of return is 3.2%. Thus, the results indicate that reaching zero-energy balances in a cost-effective manner in single-family house under the current conditions in Finland is an arduous endeavour. Highlights: Study of energy, exergy balances and cost-optimality in a Finnish residential nZEB. Bidirectional energy/exergy exchange with electricity and heat grids is investigated. Payback periods, levelized energy costs and internal rates of return are calculated. Positive energy and exergy balances can be achieved, but not cost-optimality. Export to a heating grid improves the energy balance and has economic potential.